Efektivitas Permainan Congklak Berbantuan Etnomatematika terhadap Kemampuan Berpikir Kritis Matematis Kelas II Sekolah Dasar - Ratu Asmaarobiyah; Andika Arisetyawan (Institut Agama Islam Negeri (IAIN) Curup, 2024)
Mathematical critical thinking ability is a very important thing needed in solving various problems, especially in the field of mathematics. The ethnomathematics-assisted congklak game can be a learning medium used in improving mathematical critical thinking skills. Congklak ethnomathematics is a traditional game that can teach mathematical facts, skills, concepts and principles. This study aims to determine whether there is an effectiveness of the integration of congklak game assisted by ethnomathematics on students' mathematical critical thinking skills on the material of number counting operations in grade II SD. The sample of this study was grade II SDN Cipanas. The research method used is quantitative with experimental techniques, quasi experimental design, and non-equivalent control group design which is analysed using the help of SPSS 29 for Windows. Data collection methods are tests in the form of descriptions and documentation. Based on the results of research data analysis and discussion, it is concluded that learning by using ethnomathematics-assisted congklak game media (experimental class) improves much better than learning by using a conventional method approach (control class) on students' mathematical critical thinking skills on number operations. As well as the integration of learning media in the form of ethnomathematics-assisted congklak game is considered to have moderate quality and is quite effective in providing a significant increase in students' mathematical critical thinking skills in number operations. Meanwhile, learning with a conventional method approach is considered to have low quality and is not effective in providing a significant increase in students' mathematical critical thinking skills in number operations.